A warfarin-antibiotic drug-drug interaction: a podiatric surgical case report. (2nd April 2022) - Feeney, Sally; Rees, Sharon; Modha, Ravi Krishān
Abstract : Several groups of antibiotics are known to interact with warfarin, presenting a challenge to the prescriber trying to manage underlying clinical infection, whilst mitigating the risk of coagulopathy. The authors present a case report of a 64-year old warfarinised patient who underwent forefoot surgery and developed a subsequent post-operative infection with combinations of antibiotics, leading to excessive anticoagulation and an adverse drug event. From reviewing both local and national guidance, careful monitoring is mandatory, dosing adjustments and pre-emptive dose reduction might also be needed. Consultation within the wider multi-disciplinary network will be central to decision making and implementing safety netting measures.